ANALISIS KINERJA PEGAWAI KANTOR CAMAT PINGGIR KABUPATEN BENGKALIS - CHAIRUN, M. NAZRI; YULIANI, FEBRI (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2014)
This study was to investigate the performance of the District baseboards Bengkalis and cultural factors influence the organization , leadership style , quality of human resources on the performance of the District Uptown Bengkalis . A general overview of some of the above is based on observations in the field discovered phenomena occur : ( a) . still shows a lack of employee working attitude as an employee does not comply with the existing regulations in the discipline of work and loyalty and dedication this is evidenced by the still quite high absenteeism of employees , ( b ) . still a lack of desire and awareness of employees to do the job execution completion of office in accordance with set targets to support the achievement of the implementation of the organization's work , ( c ) lack of leadership in respect of performance of subordinates and motivate subordinates work .In this study the authors use the concept of the theory according to Mangkunagara ( 2010:13 ) , the factors that affect performance are : capability (ability ) include : ( a) . knowledge (knowledge ) , ( b ) Skill . Motivation ( Motivation ) include : (a ) . Attitude ( Attitude ) , ( b ) . Working situation ( situational )The results showed that Skirting Head Office employee performance is seen from ( 1 ) capability (ability ) is here covers the knowledge and skills of employees where the capabilities of an employee in an organization that includes knowledge and skills or skills and attitudes , emphasizing measurable behavior as an application of the resulting performance , ability Uptown District Office employee is considered to be running pretty well . ( 2 ) Motivation ( motivation) is identical to the attitudes and behavior and the actions performed by the employees in the organization and their work situation .Keywords : Analysis , Performance , Employee